La Casa de Velázquez de Madrid y el Colegio de España en París: dos historias paralelas - Antonio Niño (Mélanges de la Casa de Velázquez, 2024)
The two institutions discussed in this article were conceived in the same historical circumstances and went through very similar vicissitudes. First of all, it reconstructs their common origin in the context of the First World War and the immediate post-war period. It reviews the process of construction of the Casa de Velázquez, already studied by historiography, and explains at what point the project of the Villa Carpeaux in Paris was changed to the foundation of a College of Spain in the Cité Universitaire, then in full development. The detailed analysis of the negotiations leading to the construction of this College will show the different modes of action during the constitutional regime, the dictatorship of Primo de Rivera and the Second Republic. The representative and symbolic character attributed to the two centres from the outset will also serve to show the ups and downs of bilateral relations, the inequality of exchanges and the national complexes involved in this history.